ANALISIS KUALITAS PELAYANAN LABORATORIUM MAC POLITEKNIK INDUSTRI FURNITUR DAN PENGOLAHAN KAYU - Nuskha Ilma Arini; Niki Etruly; Yessi Nasia Ulfia; Maharsi Anis Salsabila (Value : Jurnal Manajemen dan Akuntansi, 2023)
The Mac computer lab is one of the busiest labs because it is always used as a place for practice. Service satisfaction is the focus of the laboratory manager because not all customers express the level of service satisfaction directly. Therefore, researchers should analyze and find out the level of customer satisfaction with the quality of services provided to help laboratory management improve the quality of services, so that customer satisfaction will be better, The variables used in this research are tangible, reliability, responsiveness, empathy and responsibility. This variable is subjected to multiple linear regression to determine whether the variable partially and simultaneously has a significant effect on service satisfaction. The sample used was laboratory user students with data collection techniques using saturated sampling methods and Likert scales. The data are processed using multiple linear regression. From the results of data processing and discussion it is known that the tangible and assurance variables have no relationship with service satisfaction because the t count is smaller than the t table. The variables reliability, empathy and responsibility have a significant relationship with service satisfaction because they have positive t values greater than t table with values of 2.151, 2.216 and 1.642. Keywords: Laboratory, Linier regression, Satifaction Services